Synthetic Jet Actuator for Active Flow Control - Abdou, Sherif (My University, 2014)
This thesis investigates the characteristics of a long aspect ratio synthetic jet actuator and its application for the active control of the vibrations of the downstream cylinder in a tandem cylinder arrangement.
A long aspect ratio synthetic jet is produced through an axial slit along part of the length of a cylinder. The jet is excited acoustically by a pair of loudspeakers mounted at the cylinder terminations. The study compares between the performance of two different slits with aspect ratios of 273 and 773. The comparison is based on the spanwise distribution of the mean jet velocity and phase between the jet velocity fluctuations and the excitation signal. Three different frequencies and amplitudes are used to excite the speakers covering the range of frequencies used in the control application.
For both cases studied the mean centerline velocity of the jet increases with increasing the amplitude of the exciting signal, but decreases with increasing its frequency. Moreover, velocity deficits of up to 30% are evident as the midspan of the cylinder is approached from either end. Similar trends are also observed for the centerline phase distributions of the velocity fluctuations, with deficits of up to 130°. However, it is observed that for the long slit case the deficits in both the velocity and phase distributions are much larger than those for the short one.
The synthetic jet is then mounted in the upstream cylinder of a tandem cylinder arrangement to be used as a control actuator for controlling the vibrations of the downstream cylinder. A simple feedback control mechanism is used at a Reynolds
number of about 6.3x104. This Reynolds number corresponds to the case where the iii
downstream cylinder’s response is dominated with two frequency components, one at the resonance frequency of the cylinder, which is excited by broadband turbulence in the flow, and the other at the vortex shedding frequency. Both slits studied for the characterization experiments are used to compare their performance as control actuators.
Both jets produce comparable reductions in the vibration of the downstream cylinder. A reduction of about 20% in the total RMS amplitude of the vibrations signal is achieved. This amounts to a reduction of about 50% in the resonant peak and an average value of about 40% in the vortex shedding peak. The optimal values of gain and time lag of the controller are then used to investigate the effect of the jet on the flow. It is found that the short slit jet produced an effect that was traced up to 1.875 diameters downstream, while the effect of the long slit jet dropped dramatically very close to the upstream cylinder.
Keywords: Synthetic Jet; Flow Control; Flow Induced Vibration; Actuator; Tandem Cylinder; Acoustics; Acoustics, Dynamics, and Controls; Aerodynamics and Fluid Mechanics; Other Mechanical Engineering; Acoustics, Dynamics, and Controls